TAUHID DAN PENDIDIKAN DALAM PENDIDIKAN ISLAM ANAK USIA DINI - Yanti Ansari; Lydia Sartika (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
The background to this problem is a lack of understanding about monotheism and education in early childhood Islamic education so the aim of the research was to find out about monotheism and education. Tawhid is one of the most important concepts that Muslims hope to understand, possess and uphold. Meanwhile, education is an educational service that aims to develop the potential for moral values, instill moral beliefs and knowledge of worship in students. So it can be concluded that monotheism and education are related to each other. In this research, researchers use qualitative research, where research with a qualitative approach is an effort to find the truth in a field through discovering strengths or capacities in each concept. The result of this research is an increase in knowledge about the meaning of evaluation in early childhood Islamic education, so that teaching staff understand better how to implement good evaluation in school learning.